Hubungan Index Masa Tubuh dan Masa Kerja dengan Keluhan Muskoloskeletal pada Pekerja Instalasi Binatu di Rumah Sakit X - Dewi, Rini Puspita (Jurnal EnviScience (Environment Science), 2019)
Background: Musculoskeletal symtoms is tissue damage in skeletal muscle parts (joints, ligaments and tendons) which caused the body to receive a static load, or work in awkward postures repeated in a long time. Workers work in the laundry by position standing, bending, and sitting in a long time. Objective: This research aims to determine working periode and body mass indeks with musculoskeletal symtoms at worker laundry installation in Hospital X. Method: This research is a quantitative research with a cross sectional design. The subjects of research were laundry worker as much as 33 people. Data collection using questionnaire which containing question about musculoskeletal symtoms.Result: The result of the research shows that working period is significantly related to musculoskeletal symptoms. Â Conclusion: The result of this research shows that are significant relationships between working period with musculoskeletal symptomsÂ Keyword: Musculoskeletal Symptoms, Working Periode, Body Mass Indeks